Pengaruh Sanksi Perpajakan, Penggunaan e-SPT, dan Kualitas Pelayanan Fiskus pada Kepatuhan Wajib Pajak Orang Pribadi - Adnyana, I Gede Adhi; Jati, I Ketut (E-Jurnal Akuntansi, 2018)
This study aims to determine the effect of taxation sanctions, the use of e-SPT, and the service quality of tax authorities on individual taxpayer compliance registered at the Gianyar Primary Tax Service Office. Data analysis method used is multiple linear regression. This type of research is a study with primary data obtained from the answers of individual taxpayers who are registered in the Gianyar Primary Tax Office, which is the answer to a series of questions from the questionnaire submitted by researchers regarding factors that influence taxpayer compliance. The sample was determined using nonprobability sampling with accidental sampling technique. The results of this study indicate that tax sanctions, the use of e-SPT, and the quality of service of tax authorities have a positive effect on individual taxpayer compliance registered at the Gianyar Primary Tax Service Office. Keywords : taxation sanctions, use of e-spt, quality of fiscal services, personal taxpayer compliance